MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI MTS AL-HIDAYAH KARANGPLOSO MALANG: Manajemen Sarana Prasarana, Kualitas Pembelajaran, Pemeliharaan Preventif, Madrasah, Layanan Pendidikan - Na'im, Zaedun; Lufitasari, Ernika; Rahmawati, Ima (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
This study aims to describe the management of educational facilities and infrastructure and its contribution to the quality of learning at MTs Al-Hidayah Karangploso Malang. Using a descriptive qualitative method with a case study design, the research involved five informants through interviews, observations, and documentation to obtain a comprehensive understanding. Miles and Huberman’s analysis model was employed to systematically trace patterns of facilities management. The findings show that planning and procurement were relatively effective, although storage management remained suboptimal and maintenance tended to be reactive rather than preventive. Distribution of facilities adequately supported learning needs, while rehabilitation was carried out gradually based on the level of damage and usage priorities. Overall, facilities and infrastructure management contributed positively to learning comfort, student motivation, and classroom instructional effectiveness. The study recommends strengthening strategic planning, implementing preventive maintenance, and developing a sustainable asset management system to improve educational service quality consistently. The results provide practical and strategic implications for school management in enhancing learning quality through more structured facilities governance.